Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1 x 3 x 5 + 2 x 6 x 10 + 3 x 9 x 15/3 x 5 x 12 + 6 x 10 x 24 + 9 x 15 x 36 = 15 + 120 + 8100 + 1440 + 4860 = 14535
\(\frac{1\times3\times5+2\times6\times10+3\times9\times15}{3\times5\times12+6\times10\times24+9\times15\times36}\)
\(=\frac{1\times3\times5\times\left(1+2^3+3^3\right)}{3\times5\times12\times\left(1+2^3+3^3\right)}\)\(=\frac{1}{12}\)
Bài 2. > , < , = ?
5/7 < 4/3 2/5 < 6/10 1/4 = 3/12 27/36 >
2/9 7/6 > 7/9
7/2 = 2/7 15/23 < 1 27/9 > 2 14/15 < 1 51/17 < 4
Ta có : A=20/11×13 + 20/13×15 +20/15×17+...+20/53×55
A = 10 ×( 2/11×13+2/13×15+...12/53×55)
A = 10 ×(1/11-1/13+1/13-1/15+1/15-1/17+...+1/53-1/55)
A = 10 × (1/11-1/55)
A =10 × 4/55
A = 8/11
a) 15 + 3 ( x - 1 ) = 36
3 ( x - 1 ) = 36 - 15
3 ( x - 1 ) = 21
x - 1 = 21 : 3
x - 1 = 7
x = 7+1
x = 8
( x + 1 ) + ( x + 4 ) + ( x + 7 ) + ......... + ( x + 28 ) = 155
<=>(x+x+x...+x)+(1+4+...+28)=155
=>10x+145=155
=>10x=155-145
=>10x=10
=>x=1
Bài 4
35/85 = 7/17
36/108 = 1/3
25/100 = 1/4
39/52 = 3/4
Bài 8
a) 9/8 và 7/12
= 8×3=24 ; 12×2=24
=>9/8 =27/24
=> 7/12 ; 14/24
b) 3/20 và 4/15
=20×3=60 ; 15×4=60
=> 9/60 ; 16/60
Bài 9
a) \(\frac{3}{8},\frac{15}{8},\frac{9}{8},\frac{7}{8}\)
Từ lớn -> bé:
=>\(\frac{15}{8},\frac{9}{8},\frac{7}{8},\frac{3}{8}\)
b) \(\frac{4}{15},\frac{3}{5},\frac{8}{45},\frac{7}{15}=\frac{12}{45},\frac{27}{45},\frac{8}{45},\frac{21}{45}\)
Từ lớn -> bé:
=> \(\frac{3}{5},\frac{7}{15},\frac{4}{15},\frac{8}{45}\)
c) \(\frac{3}{8},\frac{4}{5},\frac{47}{40},\frac{9}{4}=\frac{15}{40},\frac{32}{40},\frac{47}{40},\frac{90}{40}\)
Từ lớn -> bé:
=>\(\frac{9}{4},\frac{47}{40},\frac{4}{5},\frac{3}{8}\)
Bài 10
a, Ta có
`x/15 < 4/15`
` <=> x < 4`
` <=> x ∈ {1 ; 2 ; 3}`
b, Ta có
`5/9 > x/9`
` <=> 5 > x`
` <=> x ∈ {1 ; 2 ; 3 ; 4}`
c, Ta có
`1 <x/8 < 11/8`
` <=> 8/8 < x/8 < 11/8`
` <=> 8 < x <11`
` <=> x ∈ {9 ; 10}`
a)7.(90+9+1)
=7.100
=700
b)3/4.(3/9+2/3)
=3/4.1
=3/4
a) ( 36 + 54 ) x 7 + 7 x 9 + 7
= ( 36 + 54 + 9 + 1 ) x 7
= 100 x 7
= 700
b) \(\frac{3}{4}\times\frac{3}{9}+\frac{3}{4}\times\frac{2}{3}\)
\(=\left(\frac{3}{9}+\frac{2}{3}\right)\times\frac{3}{4}\)
\(=1\times\frac{3}{4}\)
\(=\frac{3}{4}\)
\(x+\dfrac{2}{4}=\dfrac{15}{9}+\dfrac{3}{36}\\ x+\dfrac{2}{4}=\dfrac{7}{4}\\ x=\dfrac{5}{4}\)
\(x+\dfrac{2}{4}=\dfrac{15}{9}+\dfrac{3}{36}\)
\(x+\dfrac{2}{4}=\dfrac{5}{3}+\dfrac{1}{12}\)
\(x+\dfrac{2}{4}=\dfrac{7}{4}\)
\(x=\dfrac{7}{4}-\dfrac{2}{4}=\dfrac{5}{4}\)